Analysis Of Student Positioning In Group Discussions On The Material Of Functional Relations To Students Activeness - Jennah, Mufliatul; Subanji, Subanji (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2024)
Group discussions are an effective teaching method for enhancing collaboration and student understanding through social interaction. In this process, each group member not only contributes ideas but also actively positions themselves within the group's social structure. Positioning theory explains that the position one adopts during interactions, whether consciously or unconsciously, influences roles, power, and the dynamics of the discussion, ultimately affecting the outcomes and contributions of each member. This research aims to describe the patterns of student positioning in group discussions on the topic of function relations. The research method employed is qualitative descriptive. Data were collected by recording group discussion-based learning over four sessions, then two groups were selected for further analysis of the interactions during the discussions. Positioning theory demonstrates how students position themselves based on the interactions during group discussions. The research reveals that novice students tend to participate passively, facilitator students play a role in providing for the needs of the discussion, while expert students often make statements to provide information. There is a change in student positioning from expert to beginner, beginner to expert, facilitator to beginner, and beginner to facilitator. Additionally, some expert students and facilitator students consistently maintain their respective positions.